2019
DOI: 10.2337/dc19-1071
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Plasma Biomarkers and Diagnostic Panels for Nonalcoholic Steatohepatitis and Advanced Fibrosis in Patients With Type 2 Diabetes

Abstract: OBJECTIVE The 2019 Standards of Medical Care in Diabetes suggested that patients with nonalcoholic fatty liver disease (NAFLD) should be evaluated for liver fibrosis. However, the performance of noninvasive clinical models/scores and plasma biomarkers for the diagnosis of nonalcoholic steatohepatitis (NASH) and advanced fibrosis has not been carefully assessed in patients with type 2 diabetes mellitus (T2DM). RESEARCH DESIGN AND METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
164
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(178 citation statements)
references
References 30 publications
11
164
1
2
Order By: Relevance
“…This nding is possibly related to increasing BMI among some individuals. However, plasma ALT and AST concentrations are still regarded as better clinical indicators than other noninvasive biomarkers/scores for de nitive diagnosis of nonalcoholic steatohepatitis (NASH) and/or advanced brosis in patients with T2DM [24]. Consistently, we observed a signi cant reduction in ALT and AST levels in all participants after the intervention, which was more marked in the CIMWM than TMWM group at the end of the study period.…”
Section: Discussionsupporting
confidence: 78%
“…This nding is possibly related to increasing BMI among some individuals. However, plasma ALT and AST concentrations are still regarded as better clinical indicators than other noninvasive biomarkers/scores for de nitive diagnosis of nonalcoholic steatohepatitis (NASH) and/or advanced brosis in patients with T2DM [24]. Consistently, we observed a signi cant reduction in ALT and AST levels in all participants after the intervention, which was more marked in the CIMWM than TMWM group at the end of the study period.…”
Section: Discussionsupporting
confidence: 78%
“…| 85 CUSI recruited from hepatology clinics. 26 None of the diagnostic tests for NASH were better than plasma ALT (AUC: 0.78) (e.g. NashTest 2, HAIR,…”
Section: The Challeng E Of D Iag Nos Ing Na S H In Patients With T2dmmentioning
confidence: 99%
“…This is also our own personal experience in patients recruited in diabetes clinics. [23][24][25][26] A recent study compared several plasma biomarkers and diagnostic panels in 213 patients with T2DM not TA B L E 1 Potential mechanisms by which chronic hyperglycemia may play a role in NASH • Hepatic inflammation and oxidative stress with formation of hydrogen peroxide/hydroxyl radicals leading to hepatocyte lipid peroxidation. • Accelerate the production of advanced glycosylation endproducts (AGEs) and development of inflammation in Kupffer and hepatic stellate cells (both have receptors for AGE).…”
Section: The Challeng E Of D Iag Nos Ing Na S H In Patients With T2dmmentioning
confidence: 99%
“…In addition, it has been suggested that serum biomarkers of fibrosis, which were developed and validated in non-diabetic cohorts, underperform when applied to diabetic patients. 28 Also, the use of FIB-4 or NFS may lead to a higher proportion of patients in the intermediate category. 25 Thus, the direct use of a more specific test seems more suited to this setting ( Figure 2B).…”
Section: Diabetes Clinicsmentioning
confidence: 99%